Copper nanosheet catalyst with adjustable nanocavity content, preparation method and application
By forming a nanocavity structure on the copper nanosheet catalyst, the problem of difficulty in C-C bond coupling during electrocatalytic reduction of CO2 to ethylene is solved, and the selectivity and stability of the catalyst are significantly improved, achieving efficient ethylene production.
Patent Information
- Application Number
- CN202510186570.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-02-20
AI Technical Summary
In the prior art, when electrocatalyzed reduction of CO2 to ethylene, it is difficult to promote C-C bond coupling, and there is also a competitive reaction between other hydrocarbon products and hydrogen generation, affecting catalytic selectivity.
The copper nanosheet catalyst with adjustable nanocavity content is used to form a nanocavity structure through UV light cleaning to improve the local microenvironment of the catalyst and promote CO enrichment and C-C coupling.
The selectivity and catalytic activity of CO2 reduction to ethylene was significantly improved, the stability of the catalyst and the Faraday efficiency of ethylene were enhanced, reaching more than 73%.
Smart Images

Figure CN119776874A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal catalysts, and in particular to a copper nanosheet catalyst with adjustable nanocavity content, a preparation method and application thereof. Background Art
[0002] The widespread use of fossil fuels has disrupted the balance of the carbon cycle, leading to a sharp increase in the concentration of carbon dioxide in the atmosphere, which has made the greenhouse effect a pressing global issue. How to convert CO2 into value-added products has attracted the interest of researchers. However, CO2 is chemically inert and it is very challenging to activate CO2 under conventional environmental conditions. The electrocatalytic carbon dioxide reduction reaction (CO2RR) is one of the CO2 conversion methods and an attractive approach that provides a variety of reduction products ranging from C1 (HCOOH, CO), C2 (CH3COOH, C2H4, C2H5OH), C3 (CH3COCH3, C3H7OH), etc. through multiple proton transfer electron coupling pathways. In particular, new carbon cycle pathways and a sustainable carbon economy can be established through the electroreduction of carbon dioxide, and the electrical energy in the electroreduction of carbon dioxide can be provided by electricity generated from renewable energy.
[0003] Compared with other products, the reduction of CO2 to ethylene is more popular because it has a larger market demand and has a high value among all the reduced products. For example, ethylene is an essential chemical raw material for the polymer industry, pharmaceuticals, and synthesis of high-tech materials. In addition, ethylene can be directly used as a welding fuel or a natural gas additive. Currently, ethylene is mainly produced by cracking non-renewable petroleum at high temperatures. The production process is energy-intensive and highly polluting, which has a negative impact on the environment. In contrast, CO2RR is a green and sustainable way to selectively produce ethylene. Currently, the key challenge for the electrocatalytic reduction of CO2 to ethylene is to promote C-C bond coupling while reducing competing reactions for other hydrocarbon products and hydrogen generation.
[0004] Copper-based catalysts have been shown to have the ability to electro-reduce CO2 to ethylene. The selectivity of the reaction products of CO2RR depends largely on the surface properties and local environment of the catalyst. At the same time, slight changes in the catalyst-electrolyte interface may significantly affect the catalytic selectivity of the catalyst. Therefore, the development of new catalysts with rich catalytic interfaces and low-coordinated copper is considered to be an ideal method to improve the adsorption and desorption of ethylene intermediates. Among them, metallic copper catalysts with rich defects can maximize the active sites, optimize the energy barrier of *CO dimerization and improve the local pH of the catalyst, which is crucial for the selective production of ethylene. Summary of the invention
[0005] In order to solve the technical problems raised in the background technology, the present invention develops a method for preparing a copper nanosheet catalyst with adjustable nanocavity content, and the related materials can be applied to the direction of electrocatalytic carbon dioxide reduction to produce ethylene. The catalyst obtained by the synthesis method can enrich the CO generated during the carbon dioxide reduction process in the nanocavity and promote CC coupling. The nanocavity structure is not only conducive to improving the microenvironment around the catalyst, providing an ideal place for carbon dioxide adsorption and reduction, but also can improve the selectivity of CO2 reduction to ethylene, providing a new idea for the efficient conversion of carbon dioxide.
[0006] The present invention is implemented by the following technical solution: A method for preparing a copper nanosheet catalyst with adjustable nanocavity content, characterized in that it comprises the following steps:
[0007] Step 1, weigh 0.05-0.1g copper nitrate trihydrate and 0.1-0.2g L-ascorbic acid, place them in a beaker, add 20-30.0mL deionized water to dissolve, then add 0.1-0.2g polyvinyl pyrrolidone (PVP) and 0.1-0.2g hexamethylenetetramine, stir for 30-60 minutes, and oil bath at 80°C for 3h; after completion, collect the red product, wash it with ethanol and water several times, and place it in a vacuum drying oven at 60°C for 12h to obtain copper nanosheets;
[0008] Step 2, putting 40 mg of the collected copper nanosheets into an evaporating dish, placing the evaporating dish in a UV light cleaning machine, setting the power of the UV lamp to 200-300 W in an ozone atmosphere, setting the time to 30-120 min, turning the catalyst over, repeating the above operation, and obtaining a copper nanosheet catalyst with adjustable nanocavity content;
[0009] Preferably, when the mass ratio of copper nitrate trihydrate to PVP is 1:(1-2), increasing the usage of the two can achieve large-scale synthesis.
[0010] Preferably, the temperature at which the PVP is dissolved in water is 30 to 60° C., and the stirring time is 0.5 to 1 h.
[0011] Preferably, the catalyst is 20 mm away from the UV lamp tube.
[0012] Preferably, the power of the UV lamp is 300W, and the cleaning time is 30 to 120 minutes.
[0013] The invention provides a copper nanosheet catalyst with adjustable nanocavity content, which is prepared by the above method.
[0014] The present invention also proposes the application of a copper nanosheet catalyst with adjustable nanocavity content, which is applied to the electrocatalytic reduction of carbon dioxide.
[0015] And the specific application method includes the following steps;
[0016] 5 mg of the copper nanosheet catalyst with adjustable nanocavity content was weighed and dispersed in 300 mL of a mixed solution containing anhydrous ethanol: deionized water: Nafion in a volume ratio of 1.5:0.45:0.05, and ultrasonically dispersed for 30 min to obtain a uniformly mixed slurry;
[0017] Take 3uL of slurry and drop it on a glassy carbon electrode with a diameter of 0.3cm. After it dries naturally, use the glassy carbon electrode as the working electrode, the Ag / AgCl electrode as the reference electrode, and the 1ⅹ1cm2 platinum sheet electrode as the counter electrode to form a three-electrode system for reduction operation.
[0018] The present invention conducts an electrocatalytic dioxygen reduction test in a 0.6M K2CO3+0.4M KHCO3 electrolyte.
[0019] The present invention uses linear sweep voltammetry (LSV) to explore the electrocatalytic activity of the catalyst in the test, and the reaction is carried out by testing the change of current over time at a fixed potential by constant potential method (it), and 0.2mL of gas above the electrolytic cell is injected into the gas chromatograph during the reaction. The performance of the catalyst prepared in the present invention is compared with the precursor Cu nanosheet.
[0020] A copper nanosheet catalyst with adjustable nanocavity content prepared in the above step 3 was used as a working electrode, and an Ag / AgCl electrode was used as a reference electrode, and a 1ⅹ1 cm2 platinum sheet electrode was used as a counter electrode to form a three-electrode system. In a 0.6M K2CO3+0.4M KHCO3 electrolyte, at a constant potential of -0.82 V (vs. RHE), the electrolyte was kept at 30 mL and continuously circulated, and the stability of the catalyst was determined by measuring the Faraday efficiency of ethylene over a period of time by taking the gas above the electrolytic cell and injecting it into a gas chromatograph every 2 hours.
[0021] In this test, linear sweep voltammetry (LSV) is used to explore the electrocatalytic activity of the catalyst, and the reaction is carried out by testing the change of current over time at a fixed potential using constant potential method (it). At the same time, 0.2 mL of gas above the electrolytic cell is injected into the gas chromatograph during the reaction.
[0022] In specific applications, the pretreatment of the glassy carbon electrode: polish and clean the surface of the glassy carbon electrode with 0.05μm alumina polishing powder. Place the treated glassy carbon electrode in an aqueous solution containing 1.0mM K3Fe(CN)6 and 0.1MKCl, and observe the cyclic voltammetry (CV) curve. If the anode and cathode peaks are symmetrical, have the same peak current value (IPC / IPA=1), and the peak potential difference is about 60mV, the electrode surface is considered to be well processed, otherwise it needs to be re-polished to meet the requirements.
[0023] The present invention prepares a copper nanosheet catalyst with adjustable nanocavity content and applies it to electrocatalytic carbon dioxide reduction to produce ethylene. The electrode prepared by the present invention is subjected to linear sweep voltammetry test in the voltage range of 0 to -1.02 V vs RHE, and the electrochemical performance test is carried out in the voltage range of -0.52 to -1.02 V vs RHE. When the overpotential is about -0.82 V vs RHE, the Faraday efficiency of ethylene is about 73%.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The invention discloses a method for synthesizing a copper nanosheet catalyst with adjustable nanocavity content by using a UV light cleaning method. The scheme is simple and efficient to operate, has a short preparation time, and can be synthesized in large quantities.
[0026] The present invention utilizes a UV light cleaning method to control the power and time of the UV lamp and adjust the intensity of ultraviolet light emitted by the UV lamp to form nanocavities on the copper nanosheets. These nanocavities can improve the local microenvironment and can be used to enrich the *CO generated in the CO2RR catalytic process, promote CC coupling, and improve the performance of carbon dioxide reduction to ethylene.
[0027] The copper nanosheet catalyst with adjustable nanocavity content prepared by the present invention exhibits excellent CO2RR catalytic activity and selectivity in 0.6M K2CO3+0.4M KHCO3 electrolyte, and its current density and Faraday efficiency of ethylene are significantly higher than those of Cu catalyst, and it can maintain -77mA cm in 0.6M K2CO3+0.4M KHCO3 electrolyte. -2 The current density was 58 hours. This catalyst with high electrolysis selectivity and good stability has high practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The invention discloses an X-ray diffraction (XRD) diagram, a Raman diagram and an X-ray photoelectron spectroscopy (XPS) diagram of a copper nanosheet catalyst with adjustable nanocavity content prepared by the invention.
[0029] Figure 2This is a scanning electron microscope (SEM) image of a copper nanosheet catalyst with adjustable nanocavity content prepared by the present invention. As shown in the figure, before UV light cleaning, smooth and flat copper nanosheets are synthesized, while after UV light cleaning, many nanocavities appear on the copper nanosheets.
[0030] Figure 3 The invention discloses a N2 adsorption-desorption isotherm (BET) and a size distribution curve of a copper nanosheet catalyst with adjustable nanocavity content prepared by the invention.
[0031] Figure 4 The present invention discloses a nanocavity-rich copper nanosheet catalyst (UV-60min) and a linear voltammetric scanning curve (LSV) of the copper nanosheet catalyst in a 0.6M K2CO3+0.4M KHCO3 electrolyte filled with saturated carbon dioxide, a Faraday efficiency diagram of electrocatalytic carbon dioxide reduction to produce ethylene at different potentials, and a product distribution diagram on a gas chromatograph.
[0032] Figure 5 This is a long-term stability diagram of the nanocavity-rich copper nanosheet catalyst (UV-60min) prepared by the present invention in 0.6MK2CO3+0.4MKHCO3 electrolyte at a potential of -0.82V (vs.RHE).
[0033] In the figure, the XRD graph has a diffraction angle (2θ) on the horizontal axis and a diffraction peak intensity (Intensity) on the vertical axis; the XPS graph has a binding energy (Binging Energy) on the horizontal axis and a binding energy intensity (Intensity) on the vertical axis; the BET graph has a relative pressure (P / P0) on the horizontal axis and a pore volume (cm 3 g -1 ); linear sweep voltammetry (LSV) diagram, the horizontal axis is the applied voltage (E(V vs RHE)), and the vertical axis is the current density (Current density); the Faraday efficiency diagram of the obtained carbon dioxide reduction product, the horizontal axis is the applied voltage (E(V vs RHE)), and the vertical axis is the Faraday efficiency (FE) of the carbon dioxide reduction product; the gas chromatogram has a horizontal axis of peak time (time) and a vertical axis of peak intensity (Intensity). DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.
[0035] The chemical reagents used in the present invention are analytically pure copper nitrate trihydrate, L-ascorbic acid, hexamethylenetetramine, PVP, and deionized water. The UV light cleaning machine used in step 2 is model BZS250GF-TC.
[0036] Embodiment 1:
[0037] Weigh 0.05g of copper nitrate trihydrate and 0.1g of L-ascorbic acid into a 50mL glass reaction bottle, add 20mL of deionized water, and stir evenly. Then, add 0.1g of PVP and 0.1g of hexamethylenetetramine, stir for 0.5h, and a light yellow solution is obtained. Then, the solution is placed in an oil bath at 80°C for 3h. After the end, the red product is collected and washed several times, and placed in a vacuum drying oven at 60°C for 12h to obtain the precursor Cu nanosheet.
[0038] Weigh 40 mg of the precursor obtained in the above steps and put it into the evaporating dish. First, open the equipment drawer, adjust the height of the workpiece table from the UV lamp, place the evaporating dish in the UV light cleaning machine, turn on the power switch on the left side of the control panel, and the fan starts to run. Turn on the UV lamp according to the switch button on the upper right side of the operation panel. After a certain period of irradiation, wait for 1 to 2 minutes to take out the irradiated object, turn the material inside over, and repeat the above operation.
[0039] The catalyst prepared in Example 1 was applied to an electrolytic reduction reaction.
[0040] Test Example 1:
[0041] First, 5 mg of the catalyst was dispersed in 300 mL of a mixed solution containing anhydrous ethanol: deionized water: Nafion in a volume ratio of 1.5:0.45:0.05, and fully ultrasonically dispersed into ink. Then 3 uL of the ink was evenly applied to a glassy carbon electrode with a diameter of 0.3 cm for standby use. In addition, 0.6M K2CO3+0.4M KHCO3 electrolyte was used as a performance test. Before the test, high-purity carbon dioxide was continuously filled into the electrolyte to remove oxygen dissolved in the electrolyte. Test conditions: The linear sweep voltammetry (LSV) test range was 0 to -1.02 V vs RHE, and the scan rate was 0.05 V / s.
[0042] After testing at different voltages for 1 hour, the injection needle takes 0.2 mL of gas from the electrolytic cell after the CO2RR reaction and injects it into the gas chromatograph. After the injection is completed, the CO2RR products will appear in the detector on the gas chromatograph in sequence, and the Faraday efficiency of the corresponding carbon dioxide reduction product is calculated using the fitted standard curve.
[0043] Test Example 2:
[0044] Stability is one of the most important properties of a catalyst. The nanocavity-rich copper nanosheet catalyst (UV-60 min) obtained in Example 1 was used to perform a constant potential test. Figure 5 This is the current-time curve of a nanocavity-rich copper nanosheet catalyst subjected to a 58-hour cyclic electrolysis test at -0.82 V (vs. RHE). It can be seen that there is no obvious decrease in current and FE, further indicating that the copper nanosheet catalyst with a nanocavity structure (UV-60min) has excellent cyclic stability.
[0045] Result analysis:
[0046] As attached Figure 1 As shown in Figure 1, the catalyst was analyzed by X-ray diffractometer. The obtained diffraction peaks only existed in the (111), (200) and (220) crystal planes of copper element, and the diffraction peaks were sharp, with good crystallinity. No other impurity characteristic peaks appeared in Raman. According to the X-ray photoelectron spectroscopy, the synthesized copper nanosheets only showed Cu 2p peaks, and no Cu 2+ The satellite peaks of the X-ray photoelectron spectroscopy and the peak of the Auger electron spectrum at 569.0 eV indicate that the Cu in the sample is mainly Cu 0 ,These results show that pure phase copper nanosheets can be synthesized by UV irradiation without introducing other impurity phases.
[0047] As attached Figure 2 Scanning electron microscopy (SEM) showed that the surface of the synthesized precursor Cu nanosheets was smooth and flat, while the surface of the Cu nanosheets after UV light cleaning was obviously rough, and many nanocavities appeared on their surface. The size of the nanostructure was still maintained, and there was no structural collapse after UV light cleaning.
[0048] As attached Figure 3 As shown in Figure 2, according to the BET results, the specific surface area of the synthesized precursor Cu nanosheets is 2.27 m 3 g -1 The size is mainly concentrated in the micropore area. After UV light cleaning, the specific surface area of UV-60min is 3.04m 3 g -1 , and its size distribution is mainly concentrated in the mesoporous region (about 21 nm).
[0049] Based on all the above characterization results, the present invention can prepare copper nanosheet catalysts with adjustable nanocavity content through UV light cleaning method.
[0050] The specific method of using the nanocavity-rich copper nanosheet catalyst (UV-60min) prepared by the present invention to carry out electrocatalytic carbon dioxide reduction to produce ethylene in 0.6M K2CO3+0.4M KHCO3 electrolyte is as follows: a standard three-electrode system, the counter electrode is a platinum sheet electrode, the reference electrode is Ag / AgCl; the electrode, the electrolyte is a 0.6M K2CO3+0.4M KHCO3 mixed solution.
[0051] As attached Figure 4 As shown in the LSV test results, in an electrolyte containing 0.6M K2CO3+0.4M KHCO3, the nanocavity-rich copper nanosheet catalyst (UV-60min) prepared by the present invention has a significantly lower overpotential than that of Cu nanosheets when electrolyzed. The current density is also greater than that of Cu nanosheets at the same potential, and the CO2RR performance of the nanocavity-rich copper nanosheet catalyst (UV-60min) prepared in Example 1 and the Cu catalyst prepared in Comparative Example 1 are compared. As can be seen from the figure, the ethylene Faraday efficiency of the nanocavity-rich copper nanosheet catalyst (UV-60min) is significantly higher than that of the Cu catalyst at each potential, indicating that the nanocavity structure can effectively improve the catalytic performance of CO2RR to produce ethylene. At -0.82V (vs.RHE), the FE (C2H4) of the copper nanosheet catalyst with a nanocavity structure reaches 73%, and it is clearly observed on the gas chromatograph that the peak areas of ethylene and carbon monoxide of the nanocavity-rich copper nanosheet catalyst (UV-60min) are significantly higher than those of the Cu catalyst.
[0052] As attached Figure 5 As shown in Figure 2, in the case of 0.6M K2CO3+0.4M KHCO3 electrolyte and -0.82V (vs. RHE), the nanocavity-rich copper nanosheet catalyst prepared by the present invention (UV-60min) can maintain -77mA cm -2 The current density of 1.04 W and the Faradaic efficiency of ethylene of more than 65% for 58 h further demonstrated that the nanocavity-rich copper nanosheet catalyst (UV-60 min) had excellent stability.
[0053] The above electrochemical test results show that the nanocavity-rich copper nanosheet catalyst (UV-60min) is well used in long-term electrolysis of carbon dioxide to produce ethylene. Its catalytic activity and stability are higher than those of copper nanosheets, and it has high practical application value.
[0054] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A method for preparing a copper nanosheet catalyst with adjustable nanocavity content, characterized in that: The steps include: Step 1, weigh 0.05-0.1g copper nitrate trihydrate and 0.1-0.2g L-ascorbic acid, place them in a beaker, add 20-30.0mL deionized water to dissolve, then add 0.1-0.2g polyvinyl pyrrolidone (PVP) and 0.1-0.2g hexamethylenetetramine, stir for 30-60 minutes, and oil bath at 80°C for 3h; after completion, collect the red product, wash it with ethanol and water several times, and place it in a vacuum drying oven at 60°C for 12h to obtain copper nanosheets; Step 2: Put the collected 40 mg copper nanosheets into an evaporating dish, place the evaporating dish in a UV light cleaning machine, set the power of the UV lamp to 200-300 W in an ozone atmosphere, set the time to 30-120 minutes, turn the catalyst over, repeat the above operation, and obtain a copper nanosheet catalyst with adjustable nanocavity content.
2. The method for preparing a copper nanosheet catalyst with adjustable nanocavity content according to claim 1, characterized in that: When the mass ratio of copper nitrate trihydrate to PVP is 1:(1-2), increasing the usage of the two can achieve large-scale synthesis.
3. The method for preparing a copper nanosheet catalyst with adjustable nanocavity content according to claim 1, characterized in that: The temperature at which the PVP is dissolved in water is 30-60° C., and the stirring time is 0.5-1 h.
4. The method for preparing a copper nanosheet catalyst with adjustable nanocavity content according to claim 1, characterized in that: The catalyst is 20 mm away from the UV lamp.
5. The method for preparing a copper nanosheet catalyst with adjustable nanocavity content according to claim 1, characterized in that: The power of the UV lamp is 300W, and the cleaning time is 30 to 120 minutes.
6. A copper nanosheet catalyst with adjustable nanocavity content, characterized in that: The method is prepared by any one of claims 1 to 5.
7. An application of the copper nanosheet catalyst with adjustable nanocavity content as claimed in claim 6, characterized in that: Used for electrocatalytic reduction of carbon dioxide.
8. The application method according to claim 7, characterized in that: The method comprises the following steps: 5 mg of the copper nanosheet catalyst with adjustable nanocavity content was weighed and dispersed in 300 mL of a mixed solution containing anhydrous ethanol: deionized water: Nafion in a volume ratio of 1.5:0.45:0.05, and ultrasonically dispersed for 30 min to obtain a uniformly mixed slurry; Take 3uL of slurry and drop it on a glassy carbon electrode with a diameter of 0.3cm. After it dries naturally, use the glassy carbon electrode as the working electrode and the Ag / AgCl electrode as the reference electrode. 2 The platinum sheet electrode is used as the counter electrode to form a three-electrode system for electrolytic reduction.
Citation Information
Patent Citations
Preparation method of fluoride-free super-hydrophobic photocatalytic ultraviolet-proof textile
CN111021049A
Cited By
AgCl / CuO nano-catalyst and preparation method thereof
CN119972130A